Synthesis of zeolite x from bentonite via hydrothermal method - Srilai, Suphada; Tanwongwan, Worapak; Onpecth, Kobchai; Wongkitikun, Thanapat; Panpiemrasda, Kollayut; Panomsuwan, Gasidit; Eiad-Ua, Apiluck (My University, 2020)
Zeolite X were successfully synthesized from bentonite from Lopburi province, in Thailand using the two-step of hydrothermal method under optimum condition without calcination. The first step of hydrothermal were obtained at 200 ℃ for 3 h to remove unreacted impurity minerals such as quartz and muscovite. The secondary step of hydrothermal were obtained at 90 ℃ for 120 h for synthesis of zeolite X. The characterization of zeolite X were examined by x-ray diffraction (XRD), scanning electron microscopy (SEM), and infrared spectroscopy (FT-IR), respectively. The crystal structure of product was determined as zeolite X by XRD. The morphology of SEM images for zeolite X is octahedral shape. FTIR spectra are in accordance with the other characterization results.
Keywords: Alkaline activation; Bentonite; Hydrothermal; Zeolite X